Splendor in the Grass? A Pilot Study Assessing the Impact of Medical Marijuana on Executive Function - Gruber, Staci A.; Sagar, Kelly A.; Dahlgren, Mary K.; Racine, Megan T.; Smith, Rosemary T.; Lukas, Scott E. (Frontiers in Pharmacology, 2016)
Currently, 25 states and Washington DC have enacted full medical marijuana (MMJ) programs while 18 states allow limited access to MMJ products. Limited access states permit low (or zero) tetrahydrocannabinol (THC) and high cannabidiol (CBD) products to treat specified conditions such as uncontrolled epilepsy. Although MMJ products are derived from the same plant species as recreational MJ, they are often selected for their unique cannabinoid constituents and ratios, not typically sought by recreational users, which may impact neurocognitive outcomes. To date, few studies have investigated the potential impact of MMJ use on cognitive performance, despite a well-documented association between recreational marijuana (MJ) use and executive dysfunction. The current study assessed the impact of three months of MMJ treatment on executive function, exploring whether MMJ patients would experience improvement in cognitive functioning, perhaps related to primary symptom alleviation. As part of a larger longitudinal study, 24 patients certified for MMJ use completed baseline executive function assessments and 11 of these so far have returned for their first follow-up visit three months after initiating treatment. Results suggest that in general, MMJ patients experienced some improvement on measures of executive functioning, including the Stroop Color Word Test and Trail Making Test, mostly reflected as increased speed in completing tasks without a loss of accuracy. On self-report questionnaires, patients also indicated moderate improvements in clinical state, including reduced sleep disturbance, decreased symptoms of depression, attenuated impulsivity, and positive changes in some aspects of quality of life. Additionally, patients reported a notable decrease in their use of conventional pharmaceutical agents from baseline, with opiate use declining more than 42%. While intriguing, these findings are preliminary and warrant further investigation at additional time points and in larger sample sizes. Given the likelihood of increased MMJ use across the country, it is imperative to determine the potential impact of short- and long-term treatment on cognitive performance as well as the efficacy of MMJ treatment itself.